The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1371/journal.pntd.0000441
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum Amastigotes Enhance HIV-1 Production in Cocultures of Human Dendritic Cells and CD4+ T Cells by Inducing Secretion of IL-6 and TNF-α

Abstract: BackgroundVisceral leishmaniasis has emerged as an important opportunistic disease among patients infected with HIV-1. Both HIV-1 and the protozoan parasite Leishmania can productively infect cells of the macrophage-dendritic cell lineage.Methodology/Principal FindingsHere we demonstrate that Leishmania infantum amastigotes increase HIV-1 production when human primary dendritic cells (DCs) are cocultured together with autologous CD4+ T cells. Interestingly, the promastigote form of the parasite does not modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…This is a critical finding in that we have recently reported that HIV replication efficiencies in a wide variety of relevant cell types, including monocytes and macrophages, is directly related to the relative intra-cellular dNTP concentrations [31], [32]. Thus, the finding of elevated dNTP levels in both GM-CSF- and Leishmania -maturated human MDMs, as compared to both freshly isolated monocytes and untreated control cells, offers a novel mechanism to explain both the present results as well as prior in vitro and in vivo studies that demonstrate accelerated HIV-1 replication in both GM-CSF-treated and Leishmania co-infected patients [55], [67], [77], [78]. These results are consistent with the 200–1500 times decrease in replication competence of wild-type HIV-1 in monocytes as compared to the corresponding differentiated MDMs [33].…”
Section: Discussionmentioning
confidence: 60%
“…This is a critical finding in that we have recently reported that HIV replication efficiencies in a wide variety of relevant cell types, including monocytes and macrophages, is directly related to the relative intra-cellular dNTP concentrations [31], [32]. Thus, the finding of elevated dNTP levels in both GM-CSF- and Leishmania -maturated human MDMs, as compared to both freshly isolated monocytes and untreated control cells, offers a novel mechanism to explain both the present results as well as prior in vitro and in vivo studies that demonstrate accelerated HIV-1 replication in both GM-CSF-treated and Leishmania co-infected patients [55], [67], [77], [78]. These results are consistent with the 200–1500 times decrease in replication competence of wild-type HIV-1 in monocytes as compared to the corresponding differentiated MDMs [33].…”
Section: Discussionmentioning
confidence: 60%
“…It is estimated that HIV increases the risk of VL development in L. donovani -exposed populations by several hundred-fold [3], through either decreased resistance to a new primary infection or reactivation of a previous subclinical infection [108]. Co-infection studies in primary human monocyte-derived MΦs, DCs, and tonsillar tissue demonstrated that each pathogen has a detrimental effect on containment of the other— Leishmania infection enhances HIV replication via chronic immune activation, and that HIV promotes Leishmania infection by suppressing a protective host defense [109112]. The latter is corroborated by higher levels of L. donovani parasitemia in HIV co-infected individuals [113] and low CD4 + T cell counts despite suppression of viral load by antiretroviral therapy [114].…”
Section: Spectrum and Immunopathogenesis Of Progressive Vl In Humansmentioning
confidence: 99%
“…[778081] In addition, immunological disturbances caused by HIV are particularly favorable for the uncontrolled multiplication of the parasite.…”
Section: Hiv Immunologymentioning
confidence: 99%